Biodegradation Potential of Oil-based Drill Cuttings Encapsulated with Cement in the Soil Environment - Rim-Rukeh Akpofure (Journal of Applied Sciences and Environmental Management)
Biodegradation potential of slabs made from oil-based drill cuttings encapsulated with cement in a soil environment has been experimentally investigated. Results of soil analyses show that physico-chemical and biological characteristics of the soil environment as; pH (5.6 – 3.9), temperature (27.7 – 39.5 oC), redox potential (-114mV – (-80mV), total organic carbon (12.7% - 7.3%), sulphate (0.7 – 0.2mg/l), nitrate (6.7 – 2.2mg/l), moisture content (82-89%) and total microbial count (105 – 1013 cfu/g). Experimental results shows a mass loss of oil base drill cuttings encapsulated with cement slab during the period of the study, indicating approximate linear relationship between mass loss and time. When the log of mass-loss is plotted against time, an approximate linear relationship is obtained confirming a first-order chemical reaction for the biodegradation process. Results of the analyses of the soil sample indicate an environment that has the potential to degrade cement encapsulated oil based drill cuttings. @JASEM